AACRAO president helps to steer course in turbulent times. Issue 7 (14th September 2020) - Enos, Gary A.
Abstract : Twice since the start of 2020, Jack Miner has found himself adjusting to a new role amid a public health crisis. Miner began work as Vice Provost for Enrollment Management at the University of Cincinnati just weeks before the COVID‐19 crisis emerged, then ascended to the president's role at the American Association of Collegiate Registrars and Admissions Officers as the association was forced to cancel its April annual meeting.